Consulting report – DSB Mobile - Mitta, Ever (2017)
DSB Mobile is a small Peruvian software developing company based in Lima. DSB Mobile specializes in the development of both mobile and web applications and has worked with major companies such as Samsung, Claro & Entel. The company is composed of the General Manager, Zico Herrera, a sales manager, operations manager and both fulltime and contract based software developers that are hired based on the current demand for service. DSB Mobile has established a strong reputation and brand in Peru and is now looking to expand outside of Peru where they can introduce their software products into international markets. In their aspiration to internationalize, DSB Mobile is seeking to find out not only the most profitable markets for their company but also markets that would best align with DSB Mobiles mission. The solution to their question of expansion was to determine the best markets using a variety of both quantitative and qualitative factors. In using an IT Competitiveness report that was done by the British Software Alliance this was used as a reference point to determine the best ranked countries for IT competitiveness and the best countries to conduct business in base off of important IT indicators. Combined with software data statistics in terms of charges per project and cost of IT Consultants, this further narrowed down the scope to the most attractive, profitable and mutually beneficial market for DSB Mobile. The implementation plan proposed involved two market lines namely, the North American market line and the European Market line. The proposed solution takes into consideration different scenarios, one of them being the moderate work balance of 1 project per month, giving a total cost of $391,065 per year with a profit of $180,736. The Gantt chart outlined is intended to guide the company with the step by step implementation of this international expansion and prepare them to execute this plan in the most efficient and effective manner